The Role of Serum and Seminal Fluid Anti-Müllerian Hormone (AMH) in Differentiating Subtypes of Male Infertility. - Layih, Osama Ali; Oied Mohammed Saleh, Basil (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Infertility is the inability to conceive after one year of unprotected intercourse, with male factors accounting for about 50% of cases. Anti-Müllerian hormone (AMH), a glycoprotein belonging to the Transforming growth factor beta family, is secreted from Sertoli cells and plays a key role in male sexual differentiation. Objectives: To examine the potential role of Anti-Müllerian Hormone in differentiating the subtypes of male infertility. Methods: This case-control study was done at the Infertility Center of Al-Batool Teaching Hospital in Diyala Governorate, Iraq, by the Department of Biochemistry / College of Medicine / University of Baghdad between April 2024 and January 2025. It included 111 males, aged 20-55 years. These subjects were subdivided into four groups based on seminal fluid analysis: The Normozoospermic group (30 males), who served as the control group; the Asthenozoospermia group (29 males); the oligozoospermia group (25 males); and the idiopathic (unexplained) infertility group (27 males). Investigations included serum and seminal fluid measurements of anti-müllerian hormone using enzyme-linked immunosorbent assays. Results: The mean ±SD values of anti-müllerian hormone concentrations were significantly higher in the serum compared with the results of seminal plasma in all groups except the oligozoospermia group, where the AMH was higher than in the serum. The receiver operating characteristics (ROC) analysis revealed that Serum AMH exhibited fair to good diagnostic performance with cutoff value between (2.5-3.2 ng/ml), while seminal fluid AMH displayed lower diagnostic accuracy in distinguishing subtypes of male infertility, the cutoff value ranging from (1.75-3.83 ng/ml). Conclusion: Serum AMH levels exhibit fair to good diagnostic performance in differentiating subtypes of male infertility. Seminal fluid AMH displayed lower diagnostic accuracy across all groups, with elevated levels in oligozoospermic subjects. These findings suggest that serum AMH may be a valuable biomarker in evaluating male infertility subtypes.